THE FRAGRANCE OF VIETNAMESE CULTURE, IDENTITY AND FEMININITY: EXPLORING THE SCENT OF GREEN PAPAYA AS A CULTURAL COMMENTARY - Medha H S; M.G. Priya (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines The Scent of Green Papaya (1993), a film by Tranh Ahn Hung, set against the backdrop of 1950s Saigon, when France had a profound impact on Vietnam and the country was undergoing a tremendous change in the social and political scenario. The film portrays the complexities of Vietnamese culture, identity, and femininity deeply intertwined with Confucian values that shaped societal norms. The story of Mui, the protagonist, who embarks on a journey through two households and finds her own identity as Mrs Khuyen; the Vietnamese culture as shown in both the households and the portrayal of femininity through the characters of the mother and the daughter-in-law – all these throws ample light on the nuances of psycho-social relationships and cultural bonds and Confucian ideals. This paper aims to tease out these concepts through a close reading of the narrative, themes and cinematography. Through a close reading and in-depth analysis of mise-en-scène, sound design, and narrative structure and themes, this paper sheds light on the film’s critique of the societal role of women in the specific social backdrop. It also voices the patriarchal norms and the condition of women in Vietnamese society. This study aims to understand the intersections between cinema, gender, and culture and examines how cinema becomes a tool for societal change.